Synopsis of Orthodontic Treatment - Kumar Purva; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2007)
The book is written with an objective to guide the dental students, especially the students mastering in the branch of orthodontics, to focus on the practical aspects of management of malocclusion. The layout of the topics would explain the steps and approach to be executed for a particular case to achieve the desired final result. This includes learning about the patient$1 (Bs appraisal, typifying the case, organizing the therapy, specifying the dental and skeletal movements required, selection of appliance and planning the post-treatment retention. The book is concise in nature; hence, a list of references is also included for learning the minute details of the subject. The book would be a help to the undergraduate and postgraduate students, and the general dental practitioners as a reference guide.s
Keywords: Orthodontics and Dentofacial Orthopedics; Electronic books